Stimuler Application for Speaking Class: Senior High School Students’ Experiences - Sari, Khoiriya; Rahman, Benni Ichsanda (Universitas Islam Ahmad Dahlan (UIAD), 2025)
This study investigates the experiences and opinions of senior high school students who use the Stimuler application to enhance their English-speaking abilities. Digital resources such as Stimuler provide dynamic and captivating methods for practicing speaking as technology continues to influence language acquisition. The study focuses on the way in which students believe the app improves their motivation, confidence, and fluency. 26 North Sumatra senior high school students who have used the Stimuler app in their speaking classes are the subjects of this qualitative case study. Thematic analysis was used to examine the data that was gathered through questionnaires, semi-structured interviews, and classroom observations. The results prove that most students thought the Stimuler app helped them feel less anxious and enjoy speaking practice. Students' participation increased as a result of the application gamification features and real-time feedback, which enhanced their speaking abilities Nonetheless, certain obstacles were noted, including problems with internet access and comprehension of specific app functionalities. These results are consistent with Krashen's Affective Filter Hypothesis, which stresses the value of a low-anxiety learning environment, and Vygotsky's Constructivist Theory, which emphasizes the role of interactive tools in language learning. This study shows that the Stimuler application is a useful resource for improving students' speaking abilities, despite certain drawbacks. Enhancements like offline access and more lucid instructional guidance The findings suggest improvements such as offline access and clearer instructional support to enhance the app’s effectiveness. Future studies could examine the app's long-term effects on speaking ability as well as its use in various educational settings.